A novel optimization harmonic elimination technique for cascaded multilevel inverter - Ezzidin Hassan Aboadla; Sheroz Khan; Mohamed H. Habaebi; Teddy Surya Gunawan; Belal A. Hamida; Mashkuri Bin Yaacob; Ali Aboadla (Bulletin of Electrical Engineering and Informatics, 2019)
The main goal of utilizing Selective Harmonic Elimination (SHE) techniques in Multilevel Inverters (MLI) is to produce a high-quality output voltage signal with a minimum Total Harmonic Distortion (THD). By calculating N switching angles, SHE technique can eliminate (N-1) low order odd harmonics of the output voltage waveform. To optimized and obtained these switching angles, N of nonlinear equations should be solved using a numerical method. Modulation index (m) and duty cycle play a big role in selective harmonic elimination technique to obtain a minimum harmonic distortion and desired fundamental component voltage. In this paper, a novel Optimization Harmonic Elimination Technique (OHET) based on SHE scheme is proposed to re-mitigate Total Harmonic Distortion. The performance of seven-level H-bridge cascade inverter is evaluated using PSIM and validated experimentally by developing a purposely built microcontroller-based printed circuit board.